Moon observations from the Lagrange point L1 by the EPIC/DSCOVR spectrometer - Gorkavyi, Nick; Krotkov, Nickolay; Marshak, Alexander (Frontiers in Remote Sensing, 2026)
DSCOVR/EPIC, located at the Sun-Earth Lagrange point (L1) around 1.5 million kilometers away from Earth, can capture images of the near and far sides of the Moon in the multiple UV-VIS-NIR wavelengths. These observations were previously used only for calibration purposes. In this study, for the first time, images of the Moon taken by EPIC are treated as scientific data with a unique set of characteristics: 1. They were acquired under full-disk illumination of the Moon. 2. They were taken in 10 narrow wavelength bands—from the ultraviolet (317 nm) to the near-infrared (780 nm). 3. At each wavelength the entire lunar disk is imaged simultaneously. 4. The images can be oversampled to reduce noise levels and increase spatial resolution. These features of the lunar images allow the creation of high-quality maps of the far and near sides of the Moon in 10 quasi-monochromatic wavelength channels. These maps will serve as a reference for comparison with data from other satellites in lunar orbit. The study of multispectral images of the Moon presented in this paper reveals a significant mineralogical difference between the farside and the nearside of the Moon. We interpret the studied spectral features of the Moon as indicating an increased concentration of ilmenite (a titanium-iron oxide mineral, FeTiO3) on the nearside of the Moon, particularly in the Sea of Tranquility.